Thalidomide-induced limb abnormalities in a humanized CYP3A mouse model - Kazuki, Yasuhiro (Sci Rep, 2016)
Thalidomide is a teratogen in humans but not in rodents. It causes multiple birth defects including malformations of limbs, ears, and other organs. However, the species-specific mechanism of thalidomide teratogenicity is not completely understood. Reproduction of the human teratogenicity of thalidomide in rodents has previously failed because of the lack of a model reflecting human drug metabolism. In addition, because the maternal metabolic effect cannot be eliminated, the migration of unchanged thalidomide to embryos is suppressed, and the metabolic activation is insufficient to develop teratogenicity. Previously, we generated transchromosomic mice containing a human cytochrome P450 (CYP) 3A cluster in which the endogenous mouse Cyp3a genes were deleted. Here, we determined whether human CYP3A or mouse Cyp3a enzyme expression was related to the species difference in a whole embryo culture system using humanized CYP3A mouse embryos. Thalidomide-treated embryos with the human CYP3A gene cluster showed limb abnormalities, and human CYP3A was expressed in the placenta, suggesting that human CYP3A in the placenta may contribute to the teratogenicity of thalidomide. These data suggest that the humanized CYP3A mouse is a useful model to predict embryonic toxicity in humans.